In vitro metabolism and in vivo pharmacokinetics of bentysrepinine (Y101), an investigational new drug for anti-HBV-infected hepatitis: focus on interspecies comparison. (2nd April 2020) - Fan, Huirong; Zhang, Aijie; Liao, Cuiping; Yang, Yuanhui; Zhang, Lihua; Liu, Jianfeng; Xia, Yuanyuan; Si, Duanyun; Dong, Shiqi; Liu, Changxiao
Abstract: The objective of this study was to clarify the species differences of pharmacokinetics of Y101 (N-[N-benzoyl-O-(2-dimethylaminoethyl)-l-tyrosyl]-l-phenylalaninol hydrochloride), a derivative of herbal ingredient with anti-HBV hepatitis activity, in rats, dogs, monkeys and humans. The metabolic stability and metabolite identification studies using liver microsomes in vitro, plasma protein binding using a rapid equilibrium dialysis in vitro, pharmacokinetic studies in vivo were carried out to evaluate the interspecies differences. The toxicokinetic study in monkeys was also investigated. The metabolic profiles were similar in monkeys and humans, which were significant different from rats and dogs in vitro . In vitro plasma protein binding showed no major differences between species with medium to high protein binding rates. After single oral dose to rats, dogs, and monkeys, the absolute oral bioavailability of Y101 was 44.9%, 43.1%, and 19.2%, respectively. There was no accumulation for Y101 toxicokinetics in monkeys after oral administration for 90 d. The metabolic profiles indicated monkey was the very animal model for preclinical safety evaluation of Y101. Our results have demonstrated the favorable pharmacokinetics profile of Y101, which supports the clinical trials in humans.